2019
DOI: 10.1097/inf.0000000000002468
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Validation of Syndromic Case Definitions for Respiratory Syncytial Virus Infections in Young Infants

Abstract: Background: Respiratory syncytial virus (RSV) is a major cause of pediatric morbidity and mortality worldwide. Standardized case definitions that are applicable to variety of populations are critical for robust surveillance systems to guide decision-making regarding RSV control strategies including vaccine evaluation. Limited data exist on performance of RSV syndromic case definitions among young infants or in high-resource settings. Objective: The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Among the 42 included studies, the time periods covered ranged from 1979 to 2019 ( Table 1 ). Thirty-six were retrospective cohort studies [ 13–48 ], 3 were surveillance studies [ 1 , 2 , 49 ], 2 were case-control studies [ 50 , 51 ], and 1 was a prospective cohort study [ 52 ]. Study locations were varied: 20 were located within a single state [ 14 , 16 , 18 , 22 , 23 , 28 , 30 , 31 , 34 , 35 , 38–42 , 44 , 45 , 47 , 48 , 50 , 51 ], 8 used nationally representative databases [ 17 , 19–21 , 29 , 33 , 36 , 53 ], and 4 used nationwide death certificate data [ 25–27 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the 42 included studies, the time periods covered ranged from 1979 to 2019 ( Table 1 ). Thirty-six were retrospective cohort studies [ 13–48 ], 3 were surveillance studies [ 1 , 2 , 49 ], 2 were case-control studies [ 50 , 51 ], and 1 was a prospective cohort study [ 52 ]. Study locations were varied: 20 were located within a single state [ 14 , 16 , 18 , 22 , 23 , 28 , 30 , 31 , 34 , 35 , 38–42 , 44 , 45 , 47 , 48 , 50 , 51 ], 8 used nationally representative databases [ 17 , 19–21 , 29 , 33 , 36 , 53 ], and 4 used nationwide death certificate data [ 25–27 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-four studies only evaluated inpatient hospitalization due to RSV and/or ACB; 1 study [ 13 ] included inpatient and outpatient RSV cases confirmed by laboratory test, and another [ 43 ] incorporated inpatient, outpatient, and ED visits. Four studies included death certificate data [ 25–27 , 37 ], which were not specific to setting, and 2 were specific to ED visit data [ 36 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations